Respuesta :

kkfoug

Answer:

x = -3, y = -1

Step-by-step explanation:

Solve by substitution:

First make the second equation in terms of y:

y = -x-4

Next, since we found what y is, plug it into the first equation and solve for x:

-3x + 5(-x-4) = 4                             Plug in

-3x - 5x - 20 = 4                            Distribute

-8x - 20 = 4                                   Simplify

-8x = 24

x = -3

We have found that x = -3. To find y we need to plug x back into any of the equations. Let's do equation #2.

(-3) + y = -4                                    Plug in

y = -1                                              Simplify

So, y = -1 and x = -3. Let's check this in the first equation to make sure it is correct:

-3(-3)+ 5(-1) = 4                              Plug in

9 + (-5) = 4                                    Simplify

9 - 5 = 4

4 = 4

Since both sides are equal that means we are correct!

Hope this helps!!